MMP-9, Vertebrobasilar Ectasia and Vertebral Artery Dominance in Vertigo or Dizziness Patients With Vascular Risk Factors - Zhang, Huai Liang; Peng, Yan Fang; Zhang, Dao Pei; Li, Dan; Liu, Fei Xiang; Zhao, Min; Yin, Suo; Liang, Jia Xu; Wei, Tian Tian (Frontiers in Neurology, 2020)
Background and Purpose –Although vertebrobasilar ectasia (VBE) is diagnosed with increasing frequency, it is not clear whether this is because of altered hemodynamics caused by the effects of matrix metalloproteinases (MMPs) and/or vertebral artery dominance (VAD). Therefore, we investigate the relationship between plasma levels of MMPs and VBE in patients with vertigo or dizziness who also have vascular risk factors, in order to determine whether high levels of MMPs in VBE are independent of VAD. Methods – We prospectively studied 285 patients with vertigo or dizziness and at least one vascular risk factor. Plasma levels of MMPs, tissue inhibitor of metalloproteinases (TIMPs) and cathepsin L were measured. Subjects were classified as VBE-negative or VBE-positive, who were further classified based on the presence of VAD with magnetic resonance angiography. Acute ischemic stroke was screened by diffusion-weighted imaging, generally after bedside evaluation and the drawing of blood samples. Receiver operating characteristic (ROC) curves were applied to evaluate the utility of these potential biomarkers in predicting risk for ischemic stroke. Results – The prevalence of VBE in patients with vertigo or dizziness was 16.5%. Of the 82 patients with ischemic stroke, 14 strokes involved the cortex or subcortex. MMP-9 levels were significantly higher in the VBE-positive group than in the VBE-negative group (P = 0.022). There was a significant difference in the risk of posterior circulation ischemic stroke between the VBE-positive group and the VBE-negative group (P = 0.002). Levels of MMP-2 and cathepsin L tended to be higher in the VBE-negative group (P = 0.054, P = 0.060, respectively). Compared with the non-VAD subgroup, levels of MMP-2, -3, -9, TIMP-1, -2 and cathepsin L were similar in the VAD subgroup. ROC analysis showed that MMP-9 predicted risk for ischemic stroke (AUC = 0.582, 95%CI, 0.510-0.654, P = 0.030). Conclusions – MMP-9 was associated with VBE and independent of VAD. High levels of MMP-9 may predict risk for ischemic stroke in patients with vertigo or dizziness who also have vascular risk factors.